Enhancement of learning management system by integrating learning styles and adaptive courses - Lim, E.H. (Springer Verlag, 2017)
Learning management systems (LMS) such as LattitudeLearning, BIStrainer, Blackboard, Google Classroom and Moodle are commonly adapted by many education institutions. Most of the existing LMS are focusing on assisting teaching and learning related matters and does not take consideration in regards to the differences that existed between each individual learners. The main problem is that learners have different motivation, cognitive traits, and learning styles. This paper is examining the effect of learning styles by integrating adaptive courses into the LMS to suit according to the learner’s learning styles. The results revealed that learners exhibited different preferences in LMS environment based on different learning style. This paper focuses on taking account of the learner learning styles by incorporating adaptivity into the learning model. Based on this approach, the current Moodle based LMS has been implemented. By extending LMS with adaptivity, it will enable a support to teachers and learners. The research results are important to ensure that the courses include the features which fit to different learning styles. This will further identify the needs and characteristics of learners by responding to the learners and present them with the enhanced adaptive LMS based on the learners’ needs. © Springer International Publishing AG 2017.